Germination of vegetable seeds in composted biosludge - Dayang Christina, binti Safiee. (Universiti Malaysia Sarawak (UNIMAS), 2004)
A study was conducted to evaluate the effects of composted biosludge on the gennination of seven types of vegetables seeds. Seed gennination was assessed using the filtrate of composted biosludge at the concentrations of 0, 25, 50, 75 and 100%. Treated and untreated seeds then were placed in Plant Growth Chamber to genninate at 29° -30°C for 3 -5 days. The highest gennination percentage was for Raphanus sativus seeds which attained 100% gennination in 25% of composted biosludge. While the lowest germination percentage of seeds in composted biosludge was for Pachyrrhizus eros us which only attained a maximum gennination of 38% in 50% composted biosludge. Toxicity of composted biosludge were not significant at the value of P=O.O I for Brassica chinensis, Ipomea sp., Hibiscus esculentus, Lycopersicum e 'culentum, Raphanus sativus, and Vigna radiata in all concentrations of filtrate composted biosludge which is 0, 25, 50, 75 and 100%. Meanwhile, analysis of variance showed that there was a significant difference in gennination of P. erosus seeds at the levels of 50% and 100% composted biosludge. Composted biosludge was significantly enhanced in gennination of all types of vegetable except P. erosus seeds.